2014
DOI: 10.1088/0004-637x/782/2/73
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Different Isotopomers of Chloronium in the Interstellar Medium

Abstract: Main focus of this paper is to explore the possibility of findings two deuterated isotopomers of H 2 Cl + (Chloronium) in and around the Interstellar Medium (ISM). Presence of Chloronium ion has recently been confirmed by Herschel Space Observatory ′ s Heterodyne Instrument for the Far-Infrared (Neufeld et al. 2012). It observed para-chloronium towards six sources in the Galaxy. Existence of its deuterated isotopomers (HDCl + & D 2 Cl + ) are till date not discussed in the literature. We find that these deute… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Chemical modelling plays a very important role to understand the empirical outcome of the observational results. We use our large gas-grain chemical network (Das et al 2013, 2015a, 2015b, Majumdar et al 2014a, 2014b for the purpose of chemical modelling. We assume that gas and grains are coupled through accretion and thermal/non-thermal/cosmic ray evaporation processes.…”
Section: Chemical Modellingmentioning
confidence: 99%
“…Chemical modelling plays a very important role to understand the empirical outcome of the observational results. We use our large gas-grain chemical network (Das et al 2013, 2015a, 2015b, Majumdar et al 2014a, 2014b for the purpose of chemical modelling. We assume that gas and grains are coupled through accretion and thermal/non-thermal/cosmic ray evaporation processes.…”
Section: Chemical Modellingmentioning
confidence: 99%
“…The reason is the unavailability of any public database which provides a network with detailed deuterium chemistry along with spin chemistry of important protonated species. In the past, many authors have studied deuterium fractionation by cloning reactions involving hydrogen-bearing species (Aikawa et al (2012), Albertsson et al (2013), Albertsson et al (2014a), Das et al (2015), Majumdar et al (2014a), Majumdar et al (2014b), Roberts & Millar (2000a), Roberts & Millar (2000b), Sipilä et al (2013), Taquet et al (2014)). Among these studies, Roberts & Millar (2000a,b) reported one of the first gas-grain chemical models for deuteration, where the chemistry was limited to singly and a few doubly deuterated species along with surface chemistry only for H2 and HD molecules.…”
Section: Introductionmentioning
confidence: 99%
“…H 2 Cl + has been detected in the ISM by the Herschel Space Observatory (Lis et al 2010;Neufeld et al 2012). Since then, + H Cl 2 has also been detected by Muller et al (2014) have been observed (Muller et al 2014;Neufeld et al 2015), and the deuterated isotopologues, , are predicted to be detectable in future observations (Majumdar et al 2014).…”
Section: Introductionmentioning
confidence: 93%
“…Although the abundance of chlorine in space is rather low, the chemistry of chlorine-bearing molecules in the interstellar medium (ISM) has attracted a lot of attention over the years (e.g., Dalgarno et al 1974;Jura 1974;Blake et al 1986;Federman et al 1995;Amin 1996;Sonnentrucker et al 2006;Neufeld & Wolfire 2009;Lis et al 2010;De Luca et al 2012;Neufeld et al 2012Neufeld et al , 2015Lanza et al 2014;Majumdar et al 2014;Muller et al 2014). HCl has been of particular interest.…”
Section: Introductionmentioning
confidence: 99%